Some advances in supporting international financial management decisions - Holger Hinz (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1990)
This paper describes relevant decision areas in IFM. Based upon financial Information supplied by the subsidiaries, decision models related to internal activities in IFM have been discussed. The majority of these emphasize the improvement of the fund-allocation process. Their ability to rationalize cross-border cash transfers between subsidiaries as well as their flexibility concerning the Implementation of institutional aspects turns them into a promising research area for the future. Furthermore, to enhance IFM's performance with respect to risk implications a portfolio-type model has been proposed which may very well serve as the basis for an improved exposure management system in IFM …
Keywords: 650